2018
DOI: 10.1136/bjophthalmol-2018-312161
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve head cupping in glaucomatous and non-glaucomatous optic neuropathy

Abstract: Deeper ALD was observed in glaucoma than non-glaucomatous cupping after adjusting for choroidal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…The average LCT and LC depth of the POAG group in this study were 149.99 ± 39.17 µm and 545.51 ± 172.30 µm, respectively. This is comparable to the previous findings that LCT was between 169.39 ± 24.70 μm [30] and 215.67 ± 58.26 μm [2] and that ALCSD was between 492.0 ± 142.5 μm [16] and 614.58 ± 179.57 μm [30] in POAG eyes. The discrepancies between these studies may be attributable to the following reasons: First, the amount of LC deformation differs by race [31].…”
Section: Discussionsupporting
confidence: 81%
“…The average LCT and LC depth of the POAG group in this study were 149.99 ± 39.17 µm and 545.51 ± 172.30 µm, respectively. This is comparable to the previous findings that LCT was between 169.39 ± 24.70 μm [30] and 215.67 ± 58.26 μm [2] and that ALCSD was between 492.0 ± 142.5 μm [16] and 614.58 ± 179.57 μm [30] in POAG eyes. The discrepancies between these studies may be attributable to the following reasons: First, the amount of LC deformation differs by race [31].…”
Section: Discussionsupporting
confidence: 81%
“…However, Fard et al, 2019 15 reported comparable IOP findings between the two groups. This difference may be related to the large number of their eyes as the study of Fard et al, 2019 15 included 31 eyes of 31 patients with severe glaucoma, 33 eyes of 19 patients with non-glaucomatous cupping and 29 healthy controls eyes were also enrolled.…”
Section: Discussionmentioning
confidence: 91%
“…The temporal sector thickness parameter could be used with caution for non-GONs. The cup depth was significantly deeper with GON 8 , 12 . The macular ganglion cell-inner plexiform layer (GCIPL) showed an early reduction in GONs located in the inferotemporal and inferior sectors.…”
Section: Introductionmentioning
confidence: 87%